HUBUNGAN ANTARA POLA PEMBERIAN ASI DENGAN DURASI AMENORHOE LAKATASI DI RS. PKU MUHAMMADIYAH SURABAY - Umi Ma’rifah (Sinar : Jurnal Kebidanan, 2019)
Objective: to determine the relation of feeding patterns with the return of menstruation in breastfeeding mothers Methods: this study use analytical design with cross sectional design. Samples taken in the saturated samples from 30 breastfeeding mothers with a large population sample of 30 respondents. The independent variable is the breastfeeding pattern while the independent variable is the return of menstruation. The technique of collecting data by questionnaires, analyzed spearman rank correlation statistical test with Î± = 0.05 level. Result: respondents who experienced less breastfeeding patterns is 18 respondents (60%) and of the 18 respondents there are 18 respondents (60%) experienced a rapid return of menstruation is in the range of 0-3 months. Based on the test of the SPSS 22 statistical significance obtained significance value = 0.00 <0.05 mean H0 rejected and H1 accepted subsequently by Spearman rank correlation coefficient rs = 0.755 obtained value, which means there is a correlation concluded with the menstruation return of breastfeeding pattern to mothers Conclusion: mother with morebbreastfeeding pattern, they will experience a rapid return of menstruation more than 3 monthsKeywords: Breastfeeding pattern, Duration of Lactation AmenorhoeÂ